Achieving rough sphere-shaped ZnS with superior attenuation electromagnetic absorption performance. Issue 7 (16th January 2017) - Sun, Yan-chun; Li, Dong-ping; Yang, Ying; Fan, Li-shuang; Wu, Song; Wang, Peng; Song, Yi
Abstract : ZnS micrometer spheres were prepared via a facile hydrothermal route. Abstract : ZnS micrometer spheres were prepared via a facile hydrothermal route. Polyvinyl pyrrolidone (PVP) was used as the surfactant. By controlling the PVP content, the smooth surface of ZnS sphere was converted to a rough surface, which led to a stronger electromagnetic wave scattering intensity when used as an electromagnetic absorption absorber. ZnS microspheres with the roughest surface showed the best electromagnetic absorption property. The absorption frequency of this product at 2.0 mm was 4.2 GHz. The minimum reflection loss was nearly −35.0 dB, indicating excellent attenuation ability. The attenuation mechanism is discussed in detail and was attributed to the scattering effect.